اثر التعلم التنظيمي على الولاء التنظيمي في المؤسسة الاقتصادية - ريم, برحومة; مريم, خزان; مروة, قطوطة (University of eloued جامعة الوادي, 2020)
ملخص: تهدف الدراسة إلى إبراز مدى تأثير التعلم التنظيمي بأبعاده الخمسة إدارة المعرفة ديناميكيات التعلم تطبيق التكنولوجيا تحول المنظمة تمكين الأفراد في الولاء التنظيمي لدى مؤسسة اتصالات الجزائر بولاية الوادي, واعتمدنا لذلك على المنهج الوصفي التحليلي لإبراز المفاهيم المتعلقة بموضوع الدراسة وتحليلها واستقراء النتائج, ولتحقيق أهداف الدراسة تم تصميم الاستبيان الذي شمل 42 فقرة لجمع المعلومات الأولية, حيث تم معالجة 30 استمارة استبيان بواسطة البرنامج الإحصائي spss-v.25, وذلك باستخدام العديد من الأساليب الإحصائية منها: المتوسطات الحسابية ومعامل الارتباط والانحدار الخطي البسيط ,واختبار T واختبار التباين الأحادي, ومن أهم النتائج التي توصلت لها الدراسة وجود مستويات منخفضة من الولاء التنظيمي, عدم علاقة اثر بين التعلم التنظيمي والولاء التنظيمي في محل الدراسة كما توجد فروق ذات دلالة إحصائية حول توفر أبعاد التعلم التنظيمي في مؤسسة الاتصالات الجزائرية تعزى للمتغيرات الاسمية للعينة المدروسة .Abstract: The study aims to highlight the impact of organizational learning in its five dimensions, knowledge management, learning dynamics, application of technology, transformation of the organization, empowerment of individuals, in organizational loyalty at the Algerian Telecom Corporation in the wilaya of ElOued. Therefore, we relied on the descriptive and analytical approach to highlight the concepts related to the subject of the study, analyse and extrapolate the results. To achieve the objectives of the study, the questionnaire was designed that included 42 items to collect the primary information, as 30 questionnaires were processed by the statistical program spss-v.25, using many statistical methods, including: arithmetic averages, correlation coefficient, simple linear regression, T-test and single variance test Among the most important findings of the study was the presence of low levels of organizational loyalty.The absence of an effect relationship between organizational learning and organizational loyalty in the place of study. There are also statistically significant differences about the availability of the dimensions of organizational learning in the Algerian telecommunications institution due to the nominal variables of the studied sample.
مذكرة ماستر ادارة اعمال
Keywords: الكلمات المفتاحية: التعلم التنظيمي, الولاء التنظيمي; Key words: organizational learning, organizational loyalty